Development Of Obstacle Detection And Collision Avoidance For Micro-Aerial-Vehicle Using Multi-Ultrasonic Sensor - Dr. Anbarasu B, Surya Prakash GS, Shaajin Somson, Akshayaram A (International Journal of Modern Agriculture, 2021)
An obstacle detection and collision avoidance system are needed to detect obstacles in the Quadcopter’s flight path. An obstacle detection and collision avoidance system based on a multi-ultrasonic sensor design is proposed in this paper. An effective collision avoidance algorithm was developed using Arduino programming to detect and avoid obstacles using a multi-ultrasonic sensor, as well as to track vehicle motion in the vicinity of a possible collision zone. To avoid collisions with obstacles, the algorithm was implemented on an Arduino board, and the control signal will be transmitted from the Arduino board to the flight controller board. The proposed obstacle detection algorithm is appropriate for quadcopter real-time collision avoidance systems.